Pengembangan Media Pop Up Book Pada Pembelajaran Kooperatif tipe TGT Untuk Meningkatkan Hasil Belajar IPA Aspek Kognitif Siswa Kelas IV - Ita Mulyati; Endang Widi Winarni; Irwan Koto (UNIB Press, 2023)
The purpose of this study was to a) produce Pop Up Book learning media, b) describe the feasibility of the media and c) the effectiveness of the application to know the effectiveness of the application Pop Up Book media on TGT type cooperative learningon the results of science learning cognitive aspects of students on animal life cycle material in class IV SDN 17 Bengkulu City. The type of research used is research and development (R&D) in the ADDIE model. The types of data used are qualitative and quantitative data using interview instruments, needs analysis questionnaires, expert validation sheets, and student response questionnaires. The results of the material expert validation with a V coefficient of 0.77, the results of language validation with a V coefficient of 0.83 and the results of media validation with a V coefficient of 0.86. From the results of student responses obtained a positive response of 94.16%. Based on the results of the t test with a significance value (2-tailed) obtained 0.023 <0.025, then Ho is rejected and Ha is accepted. Based on the N-Gain test, a value of 66.20% was obtained in the experimental class and 48.17% in the control class. Thus it can be concluded thatPop Up Book media is suitable for use in learning and is quite effective in improving science learning outcomes in cognitive aspects of class IV SDN 17 Bengkulu City.